Caminhar : afeto, cartografia e experiência poética no centro de Vitória (ES) - Gomes, Karoline Rodrigues (2023)
The present research is focused on the study of walking as an artistic language and on the creative experimentation from this action in Centro, Vitória, Espírito Santo. The objectives are to explore the theoretical aspects related to walking, to search for artists that engage in this practice and explore the space in which they live, and also to stimulate personal artistic production through the study of the process of creating affective cartographies from experiences in Centro, Vitória. The research aims to deviate from the idea of a static body contemplating a work of art; for such, it proposes that through contemporary artistic objects we can interact with and in space, using our own bodies, expanding the possibilities of artistic perception through sensory experiences. To achieve these goals, we will analyze artists who use maps, informal cartographies, affective cartographies, and psychogeography to discuss urban space and the act of walking. Some examples of artists: Guy Debord, Francis Alÿs, Richard Long, Robert Smithson, Stanley Brouwn, Bas Jan Ader, among others. The research also involves experimentations, reports and personal photographs resulting from intentional walks in Centro, Vitória. In addition, a series of artworks entitled "Tramas do caminhar" will be presented, consisting of seams that demarcate the paths taken during the research